Regulation of soluble epoxide hydrolase in renal-associated diseases: insights from potential mechanisms to clinical researches - Gao, Peng; Cao, Yongtong; Ma, Liang (Frontiers in Endocrinology, 2024)
In recent years, numerous experimental studies have underscored the pivotal role of soluble epoxide hydrolase (sEH) in renal diseases, demonstrating the reno-protective effects of sEH inhibitors. The nexus between sEH and renal-associated diseases has garnered escalating attention. This review endeavors to elucidate the potential molecular mechanisms of sEH in renal diseases and emphasize the critical role of sEH inhibitors as a prospective treatment modality. Initially, we expound upon the correlation between sEH and Epoxyeicosatrienoic acids (EETs) and also addressing the impact of sEH on other epoxy fatty acids, delineate prevalent EPHX2 single nucleotide polymorphisms (SNPs) associated with renal diseases, and delve into sEH-mediated potential mechanisms, encompassing oxidative stress, inflammation, ER stress, and autophagy. Subsequently, we delineate clinical research pertaining to sEH inhibition or co-inhibition of sEH with other inhibitors for the regulation of renal-associated diseases, covering conditions such as acute kidney injury, chronic kidney diseases, diabetic nephropathy, and hypertension-induced renal injury. Our objective is to validate the potential role of sEH inhibitors in the treatment of renal injuries. We contend that a comprehensive comprehension of the salient attributes of sEH, coupled with insights from clinical experiments, provides invaluable guidance for clinicians and presents promising therapeutic avenues for patients suffering from renal diseases.